(untitled) (European Journal of Education, 2021)
The progress of technology and the complete integration of its products in our daily lives is now a reality. In addition to this, more and more young children now own their personal mobile devices, most of which have a connection to the internet. These new portable devices offer unlimited possibilities to their users, yet they also create more and more challenges in the field of learning. Inevitably, Mobile-assisted language learning (MALL) as a subcategory of Mlearning is also affected. The purpose of this paper is to present students' perceptions on the use of an application in the process of learning French as a foreign language. To this end, we developed an application for mobile devices in real teaching conditions, which respects the principles of the Common European Framework of Reference for Languages (CEFR). Experimental quantitative research was carried out in order to explore the students' experience concerning the application as a portable learning tool, completely integrated into the course. The target group we addressed was international students from various countries in Europe, Asia and America, who were taught French during a language immersion program, as part of a language stay in Saint Raphaël in France.